Perbandingan Kepuasan Publik atas Pelayanan Online dan Offline pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Selatan - Masykur, Firza agustianti; Samsul Arifai; Nuraeni Gani (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study aimed to compare public satisfaction with online and offline services at the investment service and one-stop integrated services in South Sulawesi Province as research objects. Methodology/approach: This research is a type of quantitative research with a comparative method that describes a variable or situation that is studied based on facts or what it is by using numerical data that can be obtained from questionnaire tabulations or questionnaires. Testing the hypothesis in this study using Independent Test sample t Results: The results of this study show a significant difference between public satisfaction with online services and Offline Services at the South Sulawesi Province One Stop Investment and Integrated Services Service. With this online service, the government's aim to launch the ProPTSP application to fulfill and facilitate access to licensing services, which are the authority of the province of South Sulawesi, is being realized well. Therefore, the results of this research show that the level of public satisfaction with online services is higher than that with offline services. Limitations: The thoughts, assumptions, and understandings of each respondent were different. The information provided through the questionnaire did not reflect respondents’ opinions. Contribution: This research contributes to  the investment office and one-stop integrated services of South Sulawesi Province.